Politics of Memory and Trauma in Parashu Pardhan’s Sitas - 23 and Padmabati Singh’s The Silence of Violence - Bhusal, Tilak (Journal of Tilottama, 2023)
The paper attempts to analyze the cultural politics of memory and trauma in Parashu Pardhan’s “Sitas - 23” and Padmabati Singh’s “The Silence of Violence.” In doing so, the paper, as an interpretive inquiry, utilizes as its analytical tools, insights from the theorists such as Dominick Lacapra, Cathy Caruth, Avishai Margalit, Geoffrey Hartman on psychological trauma and the politics of memory and trauma. As a qualitative inquiry, the paper is based, largely on, secondary sources such as books, journal articles and online sources. The purpose of this study, rather than discover new things, is to offer new interpretations on the topic which has been often ignored in the existing state of art. These storis recount the experiences of trauma and the narrativization against the Nepalese Maoists during the “People’s War.” The point of departure, taken in this paper, is that the memory of the stories is contaminated by the cultural ideologies during the Maoist Insurgency (sometimes termed as People’s War). Memories of the characters represented in the stories, thus, takes an ethical turn and becomes a part of the larger ideological politics. Their narrativization of the ideology-contaminated traumatic memory uses the language of demonization.